GE_GERICHTE P/17806/2023 vom 17. September 2025 - GE Cour de justice (2025)
MEURTRE;DOL ÉVENTUEL;HOMICIDE PAR NÉGLIGENCE;TORT MORAL | LCR.91.al2.leta; LCR.90.al3; CPP.117; CP.111; CP.47; CP.43; CP.19.al2; CP.49; CP.66; CPP.122; CO.41; CO.43